Effects of subglacial meltwater runoff on the ocean circulation beneath the Filchner Ice Shelf - Hus, Johanne Jahnsen (UiT Norges arktiske universitet, 2023)
Antarctic ice shelves, by restraining ice streams and affecting the discharge of grounded ice, play a critical role in the mass balance of the Antarctic ice sheet. In this study, sub-ice shelf CTD measurements and time series data from an ice shelf cavity mooring were used to detect subglacial runoff beneath the Filchner Ice Shelf. CTD measurements from four boreholes across the southern Filchner Ice Shelf show that subglacial runoff spreads along the shallower eastern and western flanks beneath the ice shelf. Analysis of the water mass properties at the easternmost borehole indicates that 32 % of the freshwater content in the upper mixed layer originates from subglacial runoff. It is hypothesized that the subglacial runoff observed at this site primarily originates from the Support Force Glacier, located approximately 182 km upstream of the drill sight. Between 2016 and 2022, six subglacial runoff events were detected by analysis of the time series data from the ice shelf cavity mooring. The subglacial runoff event shows a distinct pattern consisting of two phases. The first phase was identified through events of low source salinity, containing subglacial runoff. The events of low source salinity were followed by a rapid increase in source salinity, indicating phase 2 of the event. Anomalies of velocity, temperature, source salinity, and backscatter reveal that phase 2 of the subglacial runoff events result from a meltwaterladen ice shelf plume. These plumes, which are a result of the discharge of subglacial meltwater at the grounding line, are expected to contribute to increased basal melting in the deeper areas of the ice shelf. Analysis of current meter data shows that the meltwater plume modifies the mean current within the upper mixed layer. This is evident from increased velocities and a noticeable shift in the current direction. The sub-ice shelf data were used to approximate the subglacial runoff flux from the Support Force Glacier. From the CTD profile, a subglacial flux of 5.7 m^3 s^-1 was derived. A ...